Evaluation of parameters obtained from two systems of gait analysis - Assaf, N. D. [UNESP]; Rahal, S. C. [UNESP]; Mesquita, L. R. [UNESP]; Kano, W. T. [UNESP]; Abibe, R. B. [UNESP] (Wiley, 2019)
Background: The technical difficulties in utilising the force platform have stimulated the use and development of other gait systems. Therefore, this study aimed to compare the values of gait parameters obtained from a pressure-sensitive walkway and from a treadmill in healthy dogs during walking. Methods: Twelve healthy, privately owned, Labrador retriever dogs were used. During each trial, each dog was led across the pressure-sensitive walkway utilising a loose leash to the right of the handler. The velocity was restricted to the range of 0.9 to 1.1 m/s and the acceleration between −0.15 and 0.15 m/s2. For the treadmill, each dog also walked with leash loose on the treadmill. The treadmill speed was maintained at 0.9m/s. The temporospatial variables, and percentage of body weight distribution/percentage of pressure were evaluated between the two gait systems. Results: For both forelimbs and hind limbs, significant differences were found between stance percentage, which was higher on treadmill, and swing percentage and stride length/stance distance, which were higher on the pressure-sensitive walkway. The duty factor value was 0.57 for the pressure-sensitive walkway and 0.60 for treadmill. Clinical relevance: Each gait system has limitations, but also advantages that must be considered depending upon the variable and animal to be evaluated. The gait parameters obtained from the Tekscan pressure-sensitive walkway and Gait4Dog treadmill revealed differences in the temporospatial parameters between systems, but similarity in body-weight distribution/pressure percentage.
Keywords: body weight distribution; dog; pressure-sensitive walkway; temporospatial variables; treadmill